Shell effects in alkali metal nanowires: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Yanson, A. I.; Yanson, I. K.; Ruitenbeek, J. M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
After making a cold weld by pressing two clean metal surfaces together, and gradually separating the two pieces, a metallic nanowire is formed, which is progressively thinning down to a single atom before the contact is lost. We show evidence that the radii of such nanowires are influenced by electronic shell filling effects, in analogy to electronic shell structure in metal clusters. A modulation of the shell effect, known as supershell structure, is clearly observed. For sodium and potassium at larger diameters there is a crossover to crystalline facets with shell-closings corresponding to the completion of an additional atomic layer. We conclude that a complete analogy exists between shell structure in metallic clusters and nanowires.